2023
DOI: 10.7759/cureus.37028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Temporomandibular Disorders Between 2015-2021: A Literature Review

Abstract: The prevalence of temporomandibular disorder (TMD) is significantly high around the world. We conducted a literature review to determine the prevalence of TMD globally and in Saudi Arabia based on published studies. This review article collected 35 full-text articles after searching PubMed for TMD prevalence between 2015-2021. Assessing the prevalence of TMDs is important for several reasons, including providing an overview of the incidence of such disorders, educating the community, clarifying the gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Gender and age were not defined as exclusion criteria for this narrative review; however, TMD has been shown to present in higher frequency and severity in females than males, with peak severity between ages of 20 and 40, which is consistent with the demographic data of the patients enrolled in each study reviewed [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 62%
“…Gender and age were not defined as exclusion criteria for this narrative review; however, TMD has been shown to present in higher frequency and severity in females than males, with peak severity between ages of 20 and 40, which is consistent with the demographic data of the patients enrolled in each study reviewed [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 62%
“…1 As one of the most important indicators of socioeconomic status, educational attainment (EA) with a higher degree has been demonstrated to be associated with lower TMDs risk using both machinelearning and epidemiological techniques. [8][9][10] Moreover, both the public health and dentistry communities have advocated strategies aimed at managing modifiable lifestyle behaviours and psychological factors, such as smoking restriction and stress intervention, to curb the epidemic of TMDs. 1,11 Given the pivotal influence of education on human behaviour and well-being, we hypothesized that lifestyle choices and psychological factors may mediate the associations between EA and TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering inherent biases, confounding factors and the potential for reverse causality in observational studies, it is important to acknowledge the challenges in establishing a direct causal link between EA and TMDs. 9,10 Mendelian randomization (MR) has been extensively utilized in establishing causal relationships by leveraging specific genetic variants directly relevant to a particular exposure. 12,13 The random allocation of genetic variants during fertilization, mirroring the principles of randomised controlled trials, substantially diminishes the likelihood of confounding elements, such as sex and age, introducing bias into causal inferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of TMDs is significantly high globally. 3 Studies targeting Chinese college students and medical students showed the prevalence of TMD were 29.1% and 31.7%, respectively. 4 A Canadian survey indicated that up to 50% of adults may experience PT-related symptoms, including pain and functional disturbances in joint and muscle activity.…”
Section: Introductionmentioning
confidence: 99%